Public Opinion on the Right of Monks to Vote in the Election of Members of the House of Representatives in Village No. 1, Ban Kae Dam, Kae Dam Subdistrict, Kae Dam District, Mahasarakham Province - Jumlongnark, Worrawoot; Sayut, Phatcharatida (Journal of Law and Political Affairs, 2025)
This research aims to examine public opinion regarding the rights of monks to participate in the election of members of the House of Representatives in Village No. 1, Ban Kae Dam, Kae Dam Subdistrict, Kae Dam District, Mahasarakham Province. It is a quantitative study that employs a questionnaire as the primary research tool. The sample group consists of 265 respondents, and data were collected from January to March 2024. Data analysis was conducted using descriptive statistics, including percentages, means, and standard deviations. The study found that overall public opinion on monks’ rights to participate in elections was at a moderate level ( = 3.50). When analyzed by specific aspects, two items were rated at a high level and two at a moderate level. The average scores, ranked from highest to lowest, were as follows: the right to legal protection ( = 3.70), participation in governance ( = 3.68), equality (x ̅ = 3.44), and freedom of expression ( = 3.18). The study recommends that the political rights of monks should be carefully defined to balance religious principles with democratic values, ensuring both the protection of religious integrity and the preservation of citizens’ basic rights in a democratic society.